Commercialization of Moringa: Evidence from Southern Ethiopia - Alula Tafesse; Degiye Goshu; Fekadu Gelaw; Alelign Ademe (Cogent Economics & Finance, 2020)
The policies in Ethiopia to advance the commercial orientation of farmers need identification of challenges at farmer level and exhaustive actions to shift the farm sector. Further activities have to be done to change the country's present subsistence-oriented farm production system of different crops. The research has aimed at investigating factors determining the Moringa commercialization in southern Ethiopia. The cross-sectional survey method was used to identify 232 Moringa producing smallholder farmers from Wolaita and Gamo zones. Heckman's two-step sample selection model is adopted to find factors determining the probability of Moringa market participation and the intensity of participation. The study result revealed that the likelihood of the Moringa output market participation is influenced by the variables such as location, access to irrigation, and distance to market. On the other hand family size, per capita income, frequency of extension contact, access to irrigation, access to credit, and distance to market are among significantly influencing factors of the extent of Moringa marketing. Therefore, policy agents should mainly consider these variables on any development activities to improve Moringa marketing. Furthermore, it requires improving extension services and offering immediate practical training on techniques of market-oriented and value-added Moringa production and marketing systems.
Keywords: 330; Ethiopia; Heckman two-step sample selection model; Market participation; Moringa; smallholder farmers